The climate change mitigation impacts of active travel: Evidence from a longitudinal panel study in seven European cities. (March 2021) - Brand, Christian; Götschi, Thomas; Dons, Evi; Gerike, Regine; Anaya-Boig, Esther; Avila-Palencia, Ione; de Nazelle, Audrey; Gascon, Mireia; Gaupp-Berghausen, Mailin; Iacorossi, Francesco; Kahlmeier, Sonja; Int Panis, Luc; et al.
Highlights: First study of lifecycle carbon emissions effects of changes in active travel in cities. Changes in active travel have significant lifecycle carbon emissions benefits. Active travel substitutes for motorized travel – not just additional travel. Largest benefits from shifts from car to active travel for business, social, commuting. Methodology, metrics and findings are applicable to many cities across the globe. Abstract: Active travel (walking or cycling for transport) is considered the most sustainable and low carbon form of getting from A to B. Yet the net effects of changes in active travel on changes in mobility-related CO2 emissions are complex and under-researched. Here we collected longitudinal data on daily travel behavior, journey purpose, as well as personal and geospatial characteristics in seven European cities and derived mobility-related lifecycle CO2 emissions over time and space. Statistical modelling of longitudinal panel (n = 1849) data was performed to assess how changes in active travel, the 'main mode' of daily travel, and cycling frequency influenced changes in mobility-related lifecycle CO2 emissions. We found that changes in active travel have significant lifecycle carbon emissions benefits, even in European urban contexts with already high walking and cycling shares. An increase in cycling or walking consistently and independently decreased mobility-related lifecycle CO2 emissions, suggesting that active travel substituted for motorized travel – i.e. the increase was not just additional (induced) travel over and above motorized travel. To illustrate this, an average person cycling 1 trip/day more and driving 1 trip/day less for 200 days a year would decrease mobility-related lifecycle CO2 emissions by about 0.5 tonnes over a year, representing a substantial share of average per capita CO2 emissions from transport. The largest benefits from shifts from car to active travel were for business purposes, followed by social and recreational trips, and commuting to work or place of education. Changes to commuting emissions were more pronounced for those who were younger, lived closer to work and further to a public transport station. Even if not all car trips could be substituted by active travel the potential for decreasing emissions is considerable and significant. The study gives policy and practice the empirical evidence needed to assess climate change mitigation impacts of urban transport measures and interventions aimed at mode shift to more sustainable modes of transport. Investing in and promoting active travel whilst 'demoting' private car ownership and use should be a cornerstone of strategies to meet 'net zero' carbon targets, particularly in urban areas, while also reducing inequalities and improving public health and quality of urban life in a post-COVID-19 world.